2017
DOI: 10.3390/ijms18071382
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of IFN-γ Associated with Galectin-9 Production by Pleural Fluid Cells from a Patient with Extrapulmonary Tuberculosis

Abstract: In this study, we investigated the role of a matricellular protein galectin-9 (Gal-9) in pleural effusion related to tuberculosis (TB). Plasma and pleural fluid of a patient with extrapulmonary TB were analyzed for cytokine content by ELISA and Luminex. Peripheral blood mononuclear cells (PBMCs) and pleural fluid cells (PFCs) were examined for interferon-γ (IFN-γ) secretion by the enzyme-linked immunospot (ELISPOT) assay or IFN-γ ELISA, for apoptosis and necrosis by Cell Death Detection ELISA, and also underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Hsp90 is abundantly present in the serum of HIV-M. tuberculosis-coinfected patients (81). Galectins such as Gal3 secrete into exosomes (82) and promote redox imbalance (83), whereas Gal9 is frequently found in the plasma of TB patients (84) and reactivates HIV-1 (71). While we have characterized the proteome of M. tuberculosis exosomes derived from macrophages, it is certain that the presence of immunomodulatory proteins, lipids, and RNA of M. tuberculosis also influences HIV-1 reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 is abundantly present in the serum of HIV-M. tuberculosis-coinfected patients (81). Galectins such as Gal3 secrete into exosomes (82) and promote redox imbalance (83), whereas Gal9 is frequently found in the plasma of TB patients (84) and reactivates HIV-1 (71). While we have characterized the proteome of M. tuberculosis exosomes derived from macrophages, it is certain that the presence of immunomodulatory proteins, lipids, and RNA of M. tuberculosis also influences HIV-1 reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the level of galectin-9 (Gal-9), an apoptosis-inducing factor, is elevated in TPE, and that treatment of pleural lymphocytes with Gal-9 without antigen stimulation resulted in IFN-γ production, accompanied by apoptosis [14]. Thus, Gal-9 levels might have increased in this patient before therapy and may have decreased after therapy.…”
Section: Discussionmentioning
confidence: 81%
“…Gal-9 is also expressed in vascular endothelial cells with several functions, including modulating the phosphorylation of VEGF-receptor3 and insulin-like growth factor 1, regulating the RTK pathway, mediating the adhesion between tumoral and endothelial cells, regulating the proliferation and metastasis of tumor cells [31,32]. Rodriguez-Carrio J et al reported reduced numbers of angiogenic T cells and endothelial progenitor cells in RA patients [33], but another study found an elevated percentage of circulating angiogenic T cells that positively correlated with the percentage of endothelial progenitor cells in RA patients, which regulated VEGF levels through Akt signaling with CD147 [34].…”
Section: Discussionmentioning
confidence: 99%